Pengaruh Penggunaan Mulsa Plastik Terhadap Kelimpahan Serangga Myzus persicae pada Tanaman Cabai Rawit (Capsicum frutescens L.) - UTAMA, KADEK DWI; BAGUS, I GUSTI NGURAH; SIADI, I KETUT; NYANA, DEWA NYOMAN; SUASTIKA, GEDE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.4, No.1, Januari 2015, 2015)
ABSTRACT Effect of Plastic Mulch to Myzuspersicae Insect Abundance in Plant Cayenne Pepper ( Capsicum frutescens L.)   Cayenne Pepper is one of theimportantvegetablesgrowncommerciallyinthe tropicsandoccupythe mostextensiveacreageamongother vegetablesin Indonesian . There are fivespeciesarecommonly cultivatedchili Capsicumannuum ( red pepper), C.frutescens L( cayenne pepper), and C.chinensis , C.bacctum , C.pubescens ( chili gendot ). However,theeconomicpotentialis a typeof chili C.annuum and C.frutescens L. The purposeofthis study wastoknow theeffect of the useof plasticmulchoninsectabundance Myzus persicae oncropsandcayenne pepper . There arethree treatmentsbeing testedareplantingchiliusingblackplasticmulch( MH), a silverplasticmulch( MP) andplantingwithoutmulch or control( K). The results showedthat theuse ofblack plasticmulchandsilverplasticmulchcannotpreventaphids andwhiteflyinchillicrop, however the presence ofblackplasticmulchandsilverplasticmulchcanreduceboththe insectpopulation . Key words : Cayenne Pepper, Myzus persicae , plastic mulch
Keywords: cayenne Pepper, Myzus persicae, plastic mulch